Live Seminar: How good are current climate models at predicting agricultural impacts - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Live Seminar: How good are current climate models at predicting agricultural impacts in Africa and South Asia? Learn more about this seminar on the CGIAR Research Program on Climate Change, Agriculture and Food Security web site and download the publications: http://ow.ly/qP43Z